Participant experiences of mobile device-based diary studies - Sun, Xu; Golightly, David; Cranwell, Jo; Bedwell, Benjamin D.; Sharples, Sarah (IGI Global, 2013)
Mobile device-based diary studies have potential as contextual data capture methods that address the limitations of the traditional paper-based diary method. While there have been a number of studies that demonstrate the power of the mobile device-based diary approach, there is less known about participants’ experience of such studies. This paper presents three cases of mobile data capture to bring together user experiences of participating in diary studies and discuss how this can be fed into the design of methodology.